Numerical and test study on dynamic characteristics of the tail beam of top coal caving hydraulic supports - WU Mingke; YANG Shanguo; WANG Yao; MENG Bin; YANG Zheng; LIU Houguang (Jixie qiangdu)
In order to determine the sensitive vibration characteristic parameters of coal and gangue in the process of top coal caving and improve the intelligent identification accuracy of coal and gangue, the dynamic characteristics of the tail beam of the hydraulic support were studied. Firstly, the rigid-flexible coupling dynamic model of top coal caving hydraulic support and coal gangue was established, and the vibration acceleration of the tail beam of the hydraulic support in the process of coal caving was calculated. Secondly, the acceleration response was decomposed by variational mode decomposition (VMD) to obtain the intrinsic mode function (IMF), and the time domain and frequency domain characteristics of each IMF component were analyzed. Thirdly, the t-distributed stochastic neighborhood embedding (t-SNE) method was used to reduce the dimension of these features, and the average silhouette coefficient (ASC) of different features was calculated. The vibration characteristics of the tail beam under the impact of coal gangue were compared and studied. Finally, the bench of the top coal caving hydraulic support was built to verify the calculation results of the model. The results show that the energy, singular value, mean frequency, peak frequency, spectral centroid and frequency variance in the IMF component of the vibration acceleration of the tail beam are sensitive to the characteristics of coal and gangue, which can be used as the characteristic parameters of the coal and gangue identification.